Effect of Pre- and Post-partum Challenge Feeding on Performance and Serum Mineral Levels of Crossbred Dairy Cattle - Lasna Sahib, Pramod S, Bibin Becha B, Anu P Joseph; Thirupathy Venkatachalapathy R (Indian Journal of Dairy Science, 2022)
The present work was designed to evaluate the effects of pre-and post-partum challenge feeding on the production performance and serum mineral levels of the crossbred dairy cows under farm conditions. The work was scheduled for 21 days pre-partum to 60 days post-partum. Fourteen dry pregnant crossbred cows were divided into two equal groups and were maintained either on control diet (CN) or were challenge fed (CF) with concentrates from 21 days pre-partum to 45 days post-partum and thereafter maintained on the same diet as CN. The dry matter intake was significantly (p<0.01) higher in CF group when compared to CN group both during pre- and post-partum period. The average daily milk yield, peak yield, days to attain peak yield; the yield of fat, protein & lactose; the yield of 3.5 % fat corrected milk & energy corrected milk were statistically similar in both the groups. The efficiency of feed conversion into energy corrected milk was poorer in the CF group. Serum calcium and magnesium concentration was significantly higher in CF group (p<0.01 and p<0.05, respectively) however serum phosphorus concentration was similar. The results from this study indicated that high plane of nutrition during pre- and post-partum transition period, extending up to 45 days post-partum, did not yield any benefit over and above the group fed on par with the requirements.